Prevalence of Over-the-Counter Oral Antibiotics Usage in the Paediatric Population Prior to Hospital Visit - Devkota, Kiran; Tiwari , Damodar; Sharma, Yograj; Thapa, Narayan Bahadur; Ghimire, Anita (Journal of National Heart and Lung Society Nepal, 2026)
Background: The rise of antimicrobial resistance (AMR) poses a significant global health threat, with the over- the- counter (OTC) misuse of antibiotics being a major contributing factor.Methods: This descriptive observational study investigated the prevalence of over-the-counter (OTC) oral antibiotic usage in the paediatric population prior to hospital visits at the Department of Paediatrics and Neonatology of Bharatpur Hospital, Chitwan, Nepal. Conducted over one year from July 17, 2023, to July 15, 2024, the study randomly enrolled cases aged 0 hours to 14 years who visited the outpatient department. Data were meticulously recorded by paediatricians in the Outpatient registration book.Results: Out of 3170 paediatric patients seen during the study period, 870 (27.44%) had received antibiotics from outside over the counter prior to their hospital visit. The male-to-female ratio among the total cases was 1.36:1. The highest prevalence of OTC antibiotic use was observed in the 5 to 14 years age group, accounting for 392 (45.05%) cases, followed by the 1 to 5 years age group with 366 (42.06%) cases. The lowest usage was in the 0 to 2 months age group, with only 27 (3.1%) cases. Cefixime was the most commonly used OTC antibiotic, accounting for 218 (25.05%) of cases, followed by Amoxyclav at 164 (18.85%) and Azithromycin at 129 (14.82%).Conclusion: These findings highlight a significant prevalence of OTC oral antibiotic use in the paediatric population in this region, underscoring the need for interventions to promote rational antibiotic use and combat antimicrobial resistance.